2017
DOI: 10.1007/s10147-017-1112-3
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 expression in pancreatic ductal adenocarcinoma is a poor prognostic factor in patients with high CD8+ tumor-infiltrating lymphocytes: highly sensitive detection using phosphor-integrated dot staining

Abstract: BackgroundPancreatic ductal adenocarcinoma (PDAC) has an extremely poor prognosis. For the development of more effective immunotherapies, it is first necessary to elucidate the immunological escape mechanisms. In this study, we applied our recently developed highly sensitive immunostaining method employing fluorescent phosphor-integrated dot (PID) nanoparticles to evaluate the prevalence of programmed death ligand 1 (PD-L1) in patients with PDAC.MethodsThis study included 42 patients with PDAC who underwent pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 20 publications
2
42
0
Order By: Relevance
“…Yamaki et al . recently reported significantly poorer survival of PD‐L1 + compared to PD‐L1 − in pancreatic ductal adenocarcinoma patients presenting with CD8 + tumour infiltration. Moreover, PD‐1 expression in tumour‐associated macrophages is associated with disease progression in various human malignancies, while PD‐1/PD‐L1 blockade favours macrophage phagocytic activity and suppresses tumour progression .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Yamaki et al . recently reported significantly poorer survival of PD‐L1 + compared to PD‐L1 − in pancreatic ductal adenocarcinoma patients presenting with CD8 + tumour infiltration. Moreover, PD‐1 expression in tumour‐associated macrophages is associated with disease progression in various human malignancies, while PD‐1/PD‐L1 blockade favours macrophage phagocytic activity and suppresses tumour progression .…”
Section: Discussionmentioning
confidence: 96%
“…The cytotoxic T cell : T reg ratio may be considered as pivotal in immune checkpoint inhibitory therapies, as CD8 1 T cell expansion is associated with better overall survival in various malignancies treated with CTLA-4 and PD-1 blockade [41,42]. Yamaki et al [43] recently reported significantly poorer survival of PD-L1 1 compared to PD-L1 2 in pancreatic ductal adenocarcinoma patients presenting with CD8 1 tumour infiltration. Moreover, PD-1 expression in tumour-associated macrophages is associated with disease progression in various human malignancies, while PD-1/PD-L1 blockade favours macrophage phagocytic activity and suppresses tumour progression [44].…”
Section: F -H -F -H + F + H + F + H -F -H -F -H + F + H + F + Hmentioning
confidence: 99%
“…The prevalence of therapy resistance to these treatments is a persistent problem. PDAC patients have not benefited from single agent or combination ICI therapy (194)(195)(196) despite increased expression of PD-L1 in tumors (197)(198)(199). Significant efforts are underway to improve immunotherapy efficacy, including studies investigating regulatory B cell inhibition (e.g., Bruton's Tyrosine Kinase (BTK) inhibitors), IDO inhibition, and vaccine therapy (200).…”
Section: Pancreatic Cancermentioning
confidence: 99%
“…Multiple human studies have indicated that high PD‐L1 expression in pancreatic cancer tumors is associated with worse outcomes suggesting that targeting the PD‐1/PD‐L1 interaction may have therapeutic benefit in these patients . An early preclinical study in a mouse tumor transplant model showed that PD‐1 or PD‐L1 blockade had an anti‐tumor effect which was enhanced when given together with gemcitabine .…”
Section: Limited Success Of Traditional Immunotherapymentioning
confidence: 99%